Biomechanical evaluation of platform switching in different implant protocols: Computed tomography-based three-dimensional finite element analysis - Pessoa, Roberto S. [UNESP]; Vaz, Luis Geraldo [UNESP]; Marcantonio, Elcio [UNESP]; Sloten, Jos Vander; Duyck, Joke; Jaecques, Siegfried V.N. (My University, 2010)
Purpose: To evaluate the influence of platform switching on the biomechanical environment of implants in different placement and loading protocols. Materials and Methods: A computed tomography-based finite element model of a maxillary central incisor extraction socket was constructed containing a conical 13-mm external-hex implant with a 4.3-mm-diameter shoulder. Abutment models that were 4.3 mm and 3.8 mm in diameter were then imported and aligned to the implant. The 4.3-mm abutment edge matched perfectly the edge of the implant shoulder, while the 3.8-mm abutment assumed a platformswitching configuration. Then, immediately placed, immediately loaded, and osseointegrated (ie, conventional delayed loaded) protocols were simulated. Analysis of variance was used to interpret the data for peak equivalent strain (EQV strain) in the bone, bone-to-implant relative displacement, peak von Mises stress (EQV stress) in the abutment screw, and implant-abutment gap. Results: In the same clinical situation, the differences in the values of the assessed results were minor for abutments of different diameters. In addition, no statistically significant influence of the abutment diameter was seen on any of the evaluated biomechanical parameters, except for the bone-to-implant displacement, although this was observed in a rather low percentage. Nevertheless, a slightly higher EQV stress in the abutment screw was seen in all cases for the 3.8-mm-diameter abutment, although this was not statistically significant. Conclusion: Within the limitation of this finite element analysis, it can be concluded that a circumferential horizontal mismatch of 0.5 mm does not make an important contribution to the biomechanical environment of implants. Also, there seems to be no significant biomechanical drawback to the design rationale of reducing the abutment diameter to move the implant-abutment gap area away from the implant-bone interface. © 2010 by Quintessence Publishing Co Inc.
Keywords: Finite element analysis; Immediate implant loading; Immediate implant placement; Platform switching